Rick Steves' European Christmas - Steves, Rick, 1955-; Griffith, Simon; Griffith, Val.; Back Door Productions; Oregon Public Broadcasting ([Edmonds, Washington] : Back Door Productions, 2005)
Jin Rick Steves on a celebration of European Christmas traditions and music throughout England, Norway, France, Germany, Italy the Swiss Alps.
DVD.
Originally broadcast on public television.
Host, Rick Steves.
DVD
Closed-captioned.
Keywords: Christmas -- Europe; Christmas music; Europe -- Social life and customs; Europe -- Description and travel; Films for the hearing impaired; Travelogues (Motion pictures, television, etc.)